2012
DOI: 10.1590/s0104-11692012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Costs of most frequent nursing activities in highly dependent hospitalized patients

Abstract: This quantitative study aimed to identify the costs of the most frequent nursing activities in highly dependent hospitalized patients at a medical clinic. The non-probabilistic convenience sample corresponded to 607 observations regarding oral feeding activities (OF), blood pressure verification (BP) / heart rate (HR), body temperature checking (BTC), performance of intimate hygiene and management of feeding probe. The costs identified corresponded to R$2.40 (SD±2.64) for OF feeding; R$1.26 (SD±0.48) to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
22

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 5 publications
(6 reference statements)
2
5
0
22
Order By: Relevance
“…The average cost of US$8.70 (89.51%) for the materials integrated in the surgical LAP package, mainly related to the double and single drapes, was the most impactful in the composition of the direct processing cost (US$9.72), similar to what was found in studies that demonstrated the predominance of material costs in relation to DLC involving staff (18)(19)(20) . According to RDC 15 (6) , the reuse of repaired drapes with patches or mended cotton, presence of holes, tears, fabric wear or any impaired barrier function are not allowed when they are used as packaging.…”
Section: Discussionsupporting
confidence: 75%
“…The average cost of US$8.70 (89.51%) for the materials integrated in the surgical LAP package, mainly related to the double and single drapes, was the most impactful in the composition of the direct processing cost (US$9.72), similar to what was found in studies that demonstrated the predominance of material costs in relation to DLC involving staff (18)(19)(20) . According to RDC 15 (6) , the reuse of repaired drapes with patches or mended cotton, presence of holes, tears, fabric wear or any impaired barrier function are not allowed when they are used as packaging.…”
Section: Discussionsupporting
confidence: 75%
“…In hospital units, these costs are basically consisted of labor, materials and equipment used directly in the care process (11) .…”
Section: Methodsmentioning
confidence: 99%
“…de HD e limpeza de mobiliários componentes da unidade do paciente" e "reprocessamento de circuito extracorpóreo" os custos com materiais e medicamentos/soluções corresponderam aos valores que mais contribuíram para a composição do , semelhantemente aos resultados de outros estudos sobre custo direto de procedimentos realizados por profissionais de enfermagem (84)(85)(86)(87)(88) .…”
Section: Procedimentos éTicosunclassified
“…Na maioria desses casos os pacientes eram portadores de hipertensão arterial amplamente indicada na literatura (1,4,(113)(114)(115)(116) (117) . Portanto, a desobstrução trombótica do CDL, sempre que possível, é preferível à sua retirada tendo em vista que esta representaria aumento de riscos clínicos ao paciente que necessitaria interromper as sessões de HDC e ser submetido à reinserção de um novo CDL, o que impactaria nos custos intangíveis (81)(82)(83)(84) (117) .…”
Section: Durante O Período De Coleta De Dados Caso Os Cds Dosunclassified
See 1 more Smart Citation